Contemporary diplomatics of the civil and deceased estate case files found at the national archives of Zimbabwe. (16th March 2015) - Bhebhe, Sindiso
Abstract : Purpose: – This paper aims to discuss how the originality, authenticity, reliability and genuineness of legal records found at the National Archives of Zimbabwe (NAZ) are maintained. Provenance issues and their implications in diplomatics are also discussed. It notes that the status quo at the NAZ favours the diplomatic archiving of paper records, while electronic records are neglected. Design/methodology/approach: – The paper uses a qualitative research approach. The data will mainly be collected using document analysis augmented by observations from the NAZ. Literature in regard to the Court Legal system of Zimbabwe will be reviewed and this even includes newspaper articles. Academic research papers on the archiving of electronic records in the less developed nations and developed nations will be reviewed also. Findings: – The qualitative research approach revealed that the electronic national heritage of Zimbabwe is being lost mainly due to the archaic legislation which is silent on the management of electronic records. The results show again the violation of the sanctity of provenance principles in some selected cases. It was also found that the government is now producing both paper and electronic records, but the National Archives is only archiving paper records, the result of this being the incompleteness of records, thereby negatively affecting their diplomatics. Originality/value: – Whereas a lot has been published about the management of electronic records in the developing world, this paper does not try to duplicate that but tries to bring a new dimension into this by showing how the diplomatics of these records is affected.